Workplace surveillance: examining current instruments, limitations and legal background issues - Ulrike Hugl (Tourism & Management Studies)
Working life is increasingly characterized by strong tendencies towards control and surveillance of employees. To control and monitor employees, employers may take diverse surveillance instruments into consideration: examples may be time-tracking and access control systems, e-supported systems like chip cards, RFID (radio-frequency identification) chips, human implants, various biometric systems, computer surveillance, network monitoring software, GPS tracking, telecommunication, visual and Internet monitoring, as well as surveillance of detective agencies. Reasons for employers to monitor employees’ behavior are manifold: from an avoidance of malicious insider threats, the prevention of image damage, increased productivity, and through to reduced costs. This work starts with a fictive story of an employee, followed by a short presentation of surrounding viewpoints of organizational control and surveillance. The main part of the paper focuses on an analysis of currently used monitoring instruments and the Austrian legal framework of employee surveillance and related privacy issues.